Description of Smoking Knowledge and Behavior in Teenager - Avit, Firmina Lun; Sutrisno, Sutrisno; Hidayat, Arifin (Universitas Muhammadiyah Kalimantan Timur, 2023)
The efforts to find one's identity begin when entering adolescence accompanied by a desire to try new things including smoking, the percentage of smokers in Mahulu district is the fifth highest in Indonesia. The existence of the phenomenon of adolescents becoming more courageous in showing smoking behavior in public places caused researchers to be interested in knowing the description of smoking knowledge and behavior among adolescents at SMPN 2 Long Pahangai. This descriptive study used a questionnaire as a research instrument and involved all students who met the inclusion criteria so that 111 respondents were obtained. The results obtained were that most of them were in their early teens with 59 people, 62 women, 108 Dayak people, 45 people in class IX, 75 people who had family members who smoked. Most of them are addictive smokers, namely 30 people, use filtered cigarettes, namely 40 people, smoking duration of 1-2 years, namely 24 people, light smoker criteria (1-10 cigarettes/day), namely 42 people, and most of them are at the maintenance of smoking stage. smoking is 30 people. The conclusion obtained from this study is that most of the students at SMPN 2 Long Pahangai have a high level of knowledge about smoking, namely 96 people and most of the students at SMPN 2 Long Pahangai have non-smoking behavior, namely 62 people. It is necessary to increase education efforts regarding the dangers of smoking continuously and counseling about managing stress positively to adolescents at SMPN 2 Long Pahangai. Health education also needs to be given to parents